DETERMINANTS OF REPURCHASE INTEREST MEDIATED WITH QRIS ON CULINARY IN PEMATANGSIANTAR CITY - Fitria Halim; Nana Triapnita Nainggolan; Lora Ekana Nainggolan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The use of digital technology, especially in today's payment system, is increasingly having a significant influence on the development of business businesses, especially culinary. There is a view explaining emerging technologies to optimize the potential for collaboration and collective intelligence to design and launch stronger and more sustainable entrepreneurial initiatives. Research needs to be conducted to illustrate the influence of the use of technology, especially in payment activities, to be able to encourage the role of product quality and user experience on consumers' desire to return to enjoy existing culinary businesses. Based on the existing literature, this article describes the definition and characteristics of users of digital payment systems, namely quick response code Indonesian standard (QRIS). The related dimensions are the understanding of the use of QRIS as a payment method, frequency of use, number of transactions, number of culinary businesses of QRIS providers, transaction cost burden, transaction time, satisfaction, security, and public acceptance. The population and sample in this study are all QRIS users who visit culinary businesses in Pematangsiantar City during the months of March-April 2025. This research method uses quantitative analysis with Structural Equation Modeling (SEM). This article ends with a discussion of the results of the research, namely the use of QRIS is able to encourage quality and user experience in increasing consumer interest in repurchasing in culinary businesses in Pematangsiantar City as well as the research agenda for future studies.